2009
DOI: 10.1177/1753193409103498
|View full text |Cite
|
Sign up to set email alerts
|

Use of Wolfe Graft for the Treatment of Mucous Cysts

Abstract: Many surgical procedures have been described for the treatment of mucous cysts. We report a case series of a surgical technique that excises the cyst along with overlying skin and reconstructs the defect using a Wolfe graft harvested from the wrist crease. This technique can be applied to cysts in all locations, even those adjacent to the nail. The procedure has been performed on 51 mucous cysts with satisfactory results, a very low recurrence rate (4%) and negligible complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…However, it was frequently excised along with the cyst. In this case, the defect was closed either by a full thickness skin graft or by a local flap . In our review, we demonstrated that surgery had the highest cure rate among the five most commonly used treatments: all surgical techniques had a cure rate superior to 90% with a mean of 95%.…”
Section: Discussionmentioning
confidence: 79%
“…However, it was frequently excised along with the cyst. In this case, the defect was closed either by a full thickness skin graft or by a local flap . In our review, we demonstrated that surgery had the highest cure rate among the five most commonly used treatments: all surgical techniques had a cure rate superior to 90% with a mean of 95%.…”
Section: Discussionmentioning
confidence: 79%
“…Although the methods with shorter mean follow-up periods are greater in number, their mean follow-up periods range from 8 months to 6 years, and cure rates have been reported between 63% and 100%. 1,[7][8][9][11][12][13][14][15][16][17][18] In one review, the overall cure rate for surgical treatment was 95%. 3 Fritz and colleagues 7 claimed that the low recurrence rates reported in the literature were unrealistic owing to their short follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Many different techniques have been reported in the literature for the surgical treatment of DMP. [7][8][9][10] Despite the variety of techniques, reported cure rates are similar. 2 A combination of various methods, such as simple SE, excision of the cyst with peduncle ligation and osteophytectomy, excision of the head of the middle phalanx with the cyst, flap dissection from the PNF, en bloc excision of the PNF, capsulectomy, or synovectomy, followed by allowing secondary healing, primary closure, or repair with a flap or graft, has been applied in different series.…”
Section: Discussionmentioning
confidence: 99%